The Influence of Employee Perceptions on Withholding Income Tax Article 21 (Case Study of PDAM TIRTA BHAGASASI Bekasi Regency) - Hurriyaturrohman; Rumiasih, N.A.; Abriel Owen, Mochammad (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
This study aims to determine the effect of employee perceptions of deduction of income tax article 21 in PDAM TIRTA BHAGASASI Bekasi Regency. This type of research is quantitative and qualitative. The population of this study was the Regional Drinking Water Company (PDAM) TIRTA BHAGASASI Bekasi Regency using purposive sampling with the number of employees listed on the company profile of 1,055 to 100 respondents using the slovin formula. The research instrument is a questionnaire. The results of the research instrument test used a simple linear regression test. The significant value of the employee perception variable (X) was obtained. The tcount was 5,626 > from 1,660 and a significance of <0.050 (0.000<0.050), there was a significant effect. Based on the results of these data it can be concluded that employee perceptions affect the deduction of income tax article 21.